The Effect of Digital Financial Literacy in Mediating Hedonic Values And Risk Perception on The Intention To Invest in Gold - Eka Nurkusuma Priaswidya; Nurhidayah; Harun Al Rasyid (LP2M IAIN Palopo, 2026)
Investing in gold can be a good choice for protecting wealth and diversifying portfolios. Although there are risks involved, many investors view gold as a stable and safe asset. Hedonic values are one factor influencing people's decisions to invest in gold during the recent period of economic uncertainty. Most people purchase gold based on their desires rather than their needs. The influence of risk perception on gold investment is an important aspect that investors need to understand. Although gold is often considered a safe asset, this investment still has various risks that can affect the value and returns of the investment in the long term. Digital literacy is one of the factors required by a person in carrying out investment activities. By accessing information using digital literacy, individuals can learn about current events and predict potential risks. Improving digital literacy can contribute positively to investing, especially gold investment.